Studi Implementasi Hibah Dalam Perspektif Hukum Islam : Analisis Pelaksanaan Pemberian Hibah Dalam Kerangka Islam - Hamdan Fadhli; Aslinda Gangga Sari; Za’imatul Ulya; Youliana Youliana; Edith Pradita; Saskia Sabrina Lajadda; Sulistiyani Sulistiyani; Dwi Wulandari; Nur Rofiq (Pusat Riset dan Inovasi Nasional, 2024)
Law is a regulation or social norm that cannot be separated from the values ​​that apply in society. One of the important roles in social life that makes good education possible is the family. One of the most frequent problems is the transfer of assets from parents to children, usually in the form of gifts. In practice, many grants that are given are then canceled unilaterally by the grantor for various reasons, including wrong behavior and waste committed by the grantee. This usually happens when giving grants. Usually, the person initially displays good behavior and then changes personality over time. In the legal field, there are funding regulations that regulate requirements, procedures and legal implications. A gift is money, property, or other assets given in good faith for the benefit of the recipient. It is important to have a clear understanding of the regulatory and legal implications related to grants so that the process of granting and receiving grants is transparent and implemented in accordance with applicable regulations. This research investigates the application of funding concepts based on Islamic legal advice.